Mediation’s possible influence on legal research methodology: a window on non-doctrinal legal approaches? - Yousfi, Mourad (Debreceni Jogi Műhely, 2025)
Doctrinalism’s dominance in legal scholarship, particularly in the traditional civil law European countries, has become an accepted truth. Nevertheless, new methodologies for legal research started to emerge and take different approaches to how studying law should be. This is the situation with the multidisciplinary and interdisciplinary methodologies, which present external methods that are open to various disciplines. Thus, they contradict doctrinalism’s internal logic which is based essentially on the ‘black-letter reasoning’. Mediation is a process of a mixed sociolegal nature that we believe might boost the interest in a multidisciplinary approach, especially under the current context of the increasing regulatory tendencies encouraging recourse to this process and the failure of traditional and more formal procedures such as litigation to provide litigants with cost and time-efficient solutions. Nonetheless, it is reasonable to mention that several hurdles exist, including resistance to mediation to make this contribution. This paper aims to provide an overview of this methodological debate and the potential influence of Mediation as an Alternative Dispute Resolution (ADR) mechanism in this context.